2007
DOI: 10.1016/j.cger.2007.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Host Resistance and Immune Responses in Advanced Age

Abstract: Immunosenescence results in populating immune tissues with less functional T cells, and perhaps B cells dendritic cells, that do not function well and produce more type 2 cytokines and fewer type 1 cytokines. Impaired immunity, distinct from immunosenescence, correlates more with disease burden than chronologic age. Older adults who have chronic diseases or chronic infections are more susceptible to common infections and have poor vaccine responses. Understanding specific mechanisms and targeting interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 67 publications
(97 reference statements)
2
44
0
1
Order By: Relevance
“…In some regions, the designation of the group at the highest risk for developing active TB has shifted to the elderly. (12) In our study, we found a higher prevalence of dyspnea in patients over 60 years of age, a finding that has been reported in another study (13) and might be due to age-related changes in pulmonary function. (14) Fibrotic/atelectatic changes on chest X-rays were also more common among the patients over 60 years of age, which suggests that many of them had a history of TB.…”
Section: Discussionsupporting
confidence: 76%
“…In some regions, the designation of the group at the highest risk for developing active TB has shifted to the elderly. (12) In our study, we found a higher prevalence of dyspnea in patients over 60 years of age, a finding that has been reported in another study (13) and might be due to age-related changes in pulmonary function. (14) Fibrotic/atelectatic changes on chest X-rays were also more common among the patients over 60 years of age, which suggests that many of them had a history of TB.…”
Section: Discussionsupporting
confidence: 76%
“…One major difficulty here is to dissect the role of aging in the decreased immune response compared to the role of chronic disease, itself causing immune alterations exacerbating other chronic diseases (Castle et al 2005(Castle et al , 2007. The question is whether a high chronic disease burden leads to impaired immunity or the impaired immunity leads to high chronic disease burden or perhaps more likely, interactions in both directions.…”
Section: Frailty and Age-related Diseasesmentioning
confidence: 98%
“…The question is whether a high chronic disease burden leads to impaired immunity or the impaired immunity leads to high chronic disease burden or perhaps more likely, interactions in both directions. Recent studies at UCLA (Castle et al 2007;Rafi et al 2005) on the burden of chronic diseases used the CIRS for quantifying this parameter via the determination of health status. CIRS measures disease burden in individuals who have different chronic diseases but no evidence of acute deterioration or infection.…”
Section: Frailty and Age-related Diseasesmentioning
confidence: 99%
“…Indeed, the increased death rate found in aged populations is due in great proportion to infections (5,6) . The profound impact of ageing on immunity is presently accepted.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%